Determination of the Minimum Age Limit for Marriage: Balancing Legal Supremacy and the Objectives of Sharia in Indonesian Marriage Law - Fausi, Achmad; Asmuni, Asmuni (Fakultas Syariah UINSI Samarinda, 2024)
Based on the new Indonesian marriage law provision, marriage is only permitted if the man and woman have reached the age of 19 years. Since then, a relatively high violation of marriage law has occurred, marked by the practice of early marriages for children. Thus, the function of law as a tool of social engineering and a means of order does not work well. The research is a normative legal study that utilized the State of Law Theory, the Law Protection Theory, and the Maqāṣid Sharia to analyze the loophole in Indonesian marriage law provisions on minimum age of marriage, application for an early age marriage, officialization of unregistered early age marriage, and their practice in the Religious Court. This study reveals that the law supremacy of lowering the minimum age of marriage has the noble purpose of safeguarding religion (hifẓ al-din) through marriage at the appropriate age, the soul (hifẓ al-nafs) from the threat of death through children marriage, the mind (hifẓ al-aql) through the provision of opportunities for higher education, the offspring (hifẓ al-nasl) from the threat of stunting and miscarriages, and property (hifẓ al-māl) from the threat of poverty as a result of children being denied their right to an education. Therefore, upholding the primacy of benefit (maṣlahat) and rejecting damage is the desired outcome of the legislation limiting the age of marriage. By increasing the minimum marriage age, Indonesian law has created a breakthrough in unifying the state and Islamic legal norms, with one of its sources being 'urf (customs or practices of a society).